Mitigation of Denial of Service Attacks in Software-Defined-Cognitive Radio Networks Using Software-Defined-Cognitive Radio Shield - Mampuele, Lebepe; Velempini, Mthulisi (The Indonesian Journal of Computer Science, 2025)
A user-friendly approach to managing network resources which solve a number of management-related concerns is provided by software-defined networks. While on the other hand, a novel paradigm called Cognitive Radio Networks (CRN) was developed to address spectrum scarcity by employing dynamic spectrum access. CRN enables secondary unlicensed users to utilize the licensed spectrum when idle without interfering with authorized users. Unfortunately, the two network technologies are susceptible to security attacks. Network security planning as the first step in network protection is therefore fundamental. The techniques employed by software-defined cognitive radio networks to detect and counteract denial of service (DoS) attacks are presented in this study. We then design an intrusion detection system (IDS) to address the effects of DoS attacks. In this approach, the IDS is connected to the software-defined cognitive radio network's controller. We considered the detection time or the amount of time it takes to detect an attack, the payload, the jitter, and the packet drop rate, as evaluation metrics. The round trip time and throughput were also considered. To generate the findings and compare them to those of existing schemes we used NetSim, which was installed on the Windows 10 Operating System. The simulation results show that the proposed scheme is efficient.